2020
DOI: 10.1177/1557085120939656
|View full text |Cite
|
Sign up to set email alerts
|

Detention Experiences of Commercial Sexual Exploitation Survivors

Abstract: Commercial sexual exploitation of children (CSEC) harms youth around the globe. In the United States, most states manage CSEC victims through the juvenile justice system. Once the youth enter the system, little is known about how being detained for prostitution and solicitation charges impacts them. This study explores how CSEC survivors in Nevada experience detention through a qualitative content analysis of 36 interviews with formerly detained young women. This article offers pivotal findings reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Understanding the specific elements that contribute to youths' positive development will help guide the creation of effective CSEC specialty courts across the nation. Recent investigations that include youths' perspectives highlight the importance of specialized training for court team members (Dierkhising & Ackerman‐Brimberg, 2020) as well as opportunities for relationship building and non‐correctional housing options (Trejbalova et al, 2021). This work is challenging but invaluable and requires us as juvenile justice professionals to grapple with the purpose of the juvenile justice system, to acknowledge what is currently not working, and to be open to alternative ways of serving youth who have experienced exploitation.…”
Section: Future Directions For Serving Justice‐involved Youth Who Hav...mentioning
confidence: 99%
“…Understanding the specific elements that contribute to youths' positive development will help guide the creation of effective CSEC specialty courts across the nation. Recent investigations that include youths' perspectives highlight the importance of specialized training for court team members (Dierkhising & Ackerman‐Brimberg, 2020) as well as opportunities for relationship building and non‐correctional housing options (Trejbalova et al, 2021). This work is challenging but invaluable and requires us as juvenile justice professionals to grapple with the purpose of the juvenile justice system, to acknowledge what is currently not working, and to be open to alternative ways of serving youth who have experienced exploitation.…”
Section: Future Directions For Serving Justice‐involved Youth Who Hav...mentioning
confidence: 99%
“…The justice system often lacks trauma-informed protocols and services to adequately identify and respond to abuse or exploitation (Dierkhising & Branson, 2016; Hoefinger et al, 2019) though adolescents often experience substantial adversity and trauma prior to and during their justice involvement (Charak et al, 2019; Grasso et al, 2016; Saar et al, 2015). Moreover, research has found that CSE-impacted girls and transgender adolescents experience stigmatization, mislabeling, gender-based violence, and a general lack of agency over choices affecting their bodies while in the juvenile justice system (Godoy et al, 2020; Hammond et al, 2020; Saar et al, 2015; Trejbalová et al, 2021). These traumatic events are only compounded by repeated acts of violence (e.g., rape, sexual assault, beaten or hit with objects) and victimization (e.g., emotional abuse, forced substance use) that occur while exploited (Godoy et al, 2020; Hopper, 2017), which often results in negative physical and behavioral health outcomes, such as violence-related injuries, anxiety, depression, post-traumatic stress disorder, and suicidality (Barnert et al, 2017; Cole et al, 2016; Le et al, 2018; Palines et al, 2020).…”
Section: Introductionmentioning
confidence: 99%